PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. PRAKARSA TANI SEJATI KABUPATEN KETAPANG - Irman Irman; Dewi Kurniati; Shenny Oktoriana (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
PT. Prakarsa Tani Sejati is one of oldest company in Ketapang district. But, This company has problem about employee performance is relatively low. That is dependent by motivation and work enviroment do not support. This study aims to determine the effect of motivation and work environment on employee performance in PT Prakarsa Tani Sejati Subdistrict Sungai Laur Ketapang District. This reaserch uses Assosiatif method. The sample used was 65 respondent determined by using slovin formula. Data analysis tecnhniques used in this reaserch is multiple linear regression analysis using F test and T test. The result of multiple linear regression analysis shows that the result of F test is more than F-table thus it is concluded that employee’s motivation and work environment are equally affecting employee performance. Based on T test results known, the motivation does not affect on employee performance, while the work environment affect on performance of employees. Through determination coefficient testing obtained adjusted R square is 0,723 this means that 72,3% of variation can be explained by the Employee  performance varation of the two independent variables  work motivation and work environment. While the remaining 27,7%  is explained by reasons-other causes outside the model.